RANCANG BANGUN SISTEM PERPUSTAKAAN DIGITAL CERDAS DENGAN DETEKSI LOKASI DAN MANAJEMEN POIN TERINTREGRASI - Tegar Priyadi; Ahmat Josi; M. Hizbul Wathan (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2026)
This study designed and developed a web-based intelligent digital library system aimed at overcoming low reading interest and library visits. This system allows users to access digital book collections for free within the library environment, as well as regulate access to digital books outside the library through a point system mechanism as an incentive and control mechanism. The Prototype method was used in the development of this system, which involved the stages of requirements gathering, rapid design, and prototype evaluation. Functional testing of the system was carried out using the Blackbox Testing method. The results of the implementation show that this system has succeeded in providing easy access to digital reading materials, motivating interest in reading through a point system obtained from attendance and reading activities, and facilitating data management for librarians. The location detection feature via WiFi IP ensures that free digital book access is only available within the library zone, while access outside the zone requires point redemption. It is hoped that this system can increase users' interest in reading by combining easy access to digital information and optimising library technology.